Constructing a Religiously Ideal ',Believer', and ',Woman', in Islam - Duderija, A. author. aut Link
XIII, 258 p.
Keywords: In this comprehensive study, Adis Duderija examines how Neo Traditional Salafi thought (NTS) and progressive Muslims interpret the normative concepts of 'Believer' and 'Muslim Woman' in contemporary Islam.